1997
DOI: 10.1007/s004180050190
|View full text |Cite
|
Sign up to set email alerts
|

Hoxb-5 expression in the developing mouse lung suggests a role in branching morphogenesis and epithelial cell fate

Abstract: Hoxb-5 is one of the few homeobox genes strongly expressed in the developing mouse lung. To explore the hypothesis that Hoxb-5 acts to regulate epithelial cell fate and branching morphogenesis in the developing lung, we studied the temporal, spatial, and cell-specific expression of Hoxb-5 from gestational day (d) 13.5 to postnatal day (P) 2. Immunocytochemistry demonstrated regional localization of Hoxb-5 protein to developing conducting airways and surrounding mesenchyme. The cellular expression pattern chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 61 publications
7
62
0
Order By: Relevance
“…MiR-10a is an RA target (36) and is localized in the vicinity of the HOXB cluster of chromosome 17 in humans. The HOXB locus is involved in lung branching morphogenesis and has a putative role in determining cell fate decision in the lung (37). Our study identified nitrofen-mediated upregulation of rno-miR-10b.…”
Section: Mirnas Regulate Nitrofen-induced Airway Smooth Muscle Cell Dmentioning
confidence: 62%
“…MiR-10a is an RA target (36) and is localized in the vicinity of the HOXB cluster of chromosome 17 in humans. The HOXB locus is involved in lung branching morphogenesis and has a putative role in determining cell fate decision in the lung (37). Our study identified nitrofen-mediated upregulation of rno-miR-10b.…”
Section: Mirnas Regulate Nitrofen-induced Airway Smooth Muscle Cell Dmentioning
confidence: 62%
“…Although the precise role of SPI-3 has not been established, it could inhibit proteolytic activity and thus support neuronal survival [38]. Interestingly, Hoxb5 has also been linked to branching morphogenesis and epithelial cell fate in developing lung [39], a process which can be profoundly altered by imbalances between ECM-degrading proteinases and their inhibitors [40]. Together these studies reinforce a link between Hox genes and ECM-mediated organogenesis and differentiation.…”
Section: Towards An Integrated Picture Of the Extracellular-matrix-mementioning
confidence: 90%
“…Control lungs grew at a consistent rate from 48 through 96 h of culture (Bogue et al 1994;Aubin et al 1997;Volpe et al 1997Volpe et al , 2000Volpe et al , 2003, we evaluated Hoxb5 and Hoxa5 protein levels and immunolocalization in lungs from the RA and O 2 groups. After 48 h of 0.4 FiO 2 , Hoxb5 protein levels decreased to 50% of control lungs ( Fig.…”
Section: Fio 2 Altered Lung Morphologic Developmentmentioning
confidence: 99%